Per- and polyfluoroalkyl substances (PFAS) and heavy metals in the egg of peregrine falcon (Falco peregrinus) populations in West England, United Kingdom - Shinji Ozaki; Jacqueline S. Chaplow; Beverley Dodd; Helen Grant; M. Glória Pereira; Elaine Potter; Richard G. Sale; Darren Sleep; Sarah Thacker; Steve J. Watson; Lee A. Walker; Suzane M. Qassim (Ecotoxicology, 2026)

The importance of in-year seasonal fluctuations for biomonitoring of apex predators: A case study of 14 essential and non-essential elements in the liver of the common buzzard (Buteo buteo) in the United Kingdom - Shinji Ozaki; Paola Movalli; Alessandra Cincinelli; Nikiforos Alygizakis; Alexander Badry; Jacqueline S. Chaplow; Daniela Claßen; René W.R. J. Dekker; Beverley Dodd; Guy Duke; Jan Koschorreck; M. Glória Pereira; et al. (Environmental Pollution, 2023)

Long-term change in calcareous grassland vegetation and drivers over three time periods between 1970 and 2016 - Lucy E. Ridding; James M. Bullock; Oliver L. Pescott; Peter Hawes; Robin Walls; M. Glória Pereira; Sarah A. Thacker; Patrick O. Keenan; Ulrike Dragosits; Richard F. Pywell (Plant Ecology, 2020)
Analysis of long-term vegetation change is limited. Furthermore most studies evaluating change only examine two snapshots in time, which makes it difficult to define rates of change and accurately assess potential drivers. To assess long-term change in calcareous grassland over multiple time periods, we re-surveyed a transect study undertaken at Parsonage Down National Nature Reserve, Wiltshire, southern England in 1970 and 1990 by T. Wells. We examined differences in soil properties and species traits in each of the survey years to understand potential drivers of vegetation change, including nitrogen deposition and grazing management. There was a clear shift in species composition, combined with significant declines in species richness and diversity between 1970 and 2016, with the greater rate of change occurring between 1990 and 2016. A significant increase in soil total nitrogen was found, which was significantly associated with the decline in species diversity between 1970 and 1990. Significant changes in community-weighted mean traits were identified for plant height (increasing), specific leaf area (decreasing), grazing tolerance (decreasing) and Ellenberg N (decreasing) between 1970 and 2016. By using survey data from multiple time periods, we suggest that N deposition may have contributed towards community changes between 1970 and 1990, as indicated by the change in soil properties and the associated decline in species diversity. Vegetation change between 1990 and 2016 is likely to be largely attributable to a decline in grazing pressure, indicated by the increase in taller species and a decrease in grazing tolerance.

An investigation of the distribution of phosphorus between free and mineral associated soil organic matter, using density fractionation - Jessica L. Adams; Edward Tipping; Sarah A. Thacker; John N. Quinton (Plant and Soil, 2018)